Measurement of the mass and production rate of [xi] b [bar] baryons - Aaij, Roel; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; Comerma-Montells, Albert; D'Argent, Philippe; De Cian, Michel; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Grünberg, Oliver; Han, Xiaoxue; et al. (Physical review, 2019)
The first measurement of the production rate of Ξ−b baryons in pp collisions relative to that of Λ0b baryons is reported, using data samples collected by the LHCb experiment, and corresponding to integrated luminosities of 1, 2 and 1.6 fb−1 at √s=7, 8 and 13 TeV, respectively. In the kinematic region 2<η<6 and pT<20 GeV/c, we measure fΞ−bfΛ0bB(Ξ−b→J/ψΞ−)B(Λ0b→J/ψΛ)=(10.8±0.9±0.8)×10−2 [√s=7,8 TeV], fΞ−bfΛ0bB(Ξ−b→J/ψΞ−)B(Λ0b→J/ψΛ)=(13.1±1.1±1.0)×10−2 [√s=13 TeV], where fΞ−b and fΛ0b are the fragmentation fractions of b quarks into Ξ−b and Λ0b baryons, respectively; B represents branching fractions; and the uncertainties are due to statistical and experimental systematic sources. The values of fΞ−b/fΛ0b are obtained by invoking SU(3) symmetry in the Ξ−b→J/ψΞ− and Λ0b→J/ψΛ decays. Production asymmetries between Ξ−b and ¯Ξ+b baryons are also reported. The mass of the Ξ−b baryon is also measured relative to that of the Λ0b baryon, from which it is found that m(Ξ−b)=5796.70±0.39±0.15±0.17 MeV/c2, where the last uncertainty is due to the precision on the known Λ0b mass. This result represents the most precise determination of the Ξ−b mass.
LHCb Collaboration: R. Aaij, P. d’Argent, S. Bachmann, D. Berninghoff, S. Braun, M. Brodski, A. Comerma-Montells, M. De Cian, M. Dziewiecki, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, J. Hu, M. Kecke, M. Kolpin, R. Kopecna, B. Leverington, H. Malygina, J. Marks, D.S. Mitzel, S. Neubert, A. Piucci, N. Skidmore, M. Stahl, S. Stemmle, U. Uwer, A. Zhelezov [und weitere]
Gesehen am 24.07.2019
Im Titel steht der Buchstabe b mit einem Oberstrich